Research Progress of Nursing Care for Elderly Patients With Complicating Postoperative Hip Fracture Deep Vein Thrombosis in China (International Journal of Studies in Nursing, 2021)
Introduction: The aging of China's population has further deepened, and according to the results of the seventh national census, the population aged 60 years and above in China was 264.02 million, accounting for 18.70% (China.2021).The rapid growth of the elderly population has led to an increase a geriatric orthopedic morbidity. The hip fracture is one of the common orthopedic diseases, which has posed a severe threat to the elderly's life and health (Yu, 2019). Purpose: In this study, we investigated the domestic and international literature, focusing on the analysis of DVT nursing prevention programs for elderly patients after hip arthroplasty, and proposed the current nursing research progress in preventing DVT to help elderly patients actively cope with DVT, improve the quality of life in later life, and make DVT a truly preventable disease. Method: Electronic searches using scholarly databases were employed and only significant articles that met the review objective were utilized. Findings: Currently, the main treatment option for hip fracture patients in clinical practice is surgery, and how to prevent Deep Vein Thrombosis (DVT) is an important task in the postoperative care of elderly orthopedic patients (Li, 2016). Research studies have shown that all elderly patients are at a very high risk of DVT during hospitalization, but the current trend is that 50% of patients at high risk of thrombosis are still not actively and effectively prevented from developing thrombosis for various reasons. Conclusion: This disease, which has a high incidence, a high mortality rate, and is difficult to prevent, requires increased attention and necessitates exploration to derive effective nursing intervention programs and related nursing measures to prevent reduce the formation of DVT and alleviate suffering for patient (Xu, 2016). In this review, we summarized the main nursing methods for preventing deep vein thrombosis of the lower extremities after hip fracture surgery in the elderly. Elderly patients are a special group of people, both physically and psychologically in a relatively fragile state, especially after the operation, so they need to be more careful in nursing work. In addition to general physical care, the care of their psychological state is also extremely important. This article describes in detail the physiological and psychological nursing interventions for patients, which can effectively guide and help medical staff to cope with the clinical care of such patients, and enable patients to better recover from surgery and trauma, and obtain a good prognosis.